BS EN 4630. Aerospace series. Steel X4CrNiMo16-5-1 (1.4418). Air melted. Hardened and tempered. Forgings. De ≤ 200 mm. 900 MPa ≤ Rm ≤ 1 050 MPa. (23rd June 2021) - British Standards Institution,
No abstract available